Nanotopography-driven changes in focal adhesion morphology of human dermal fibroblast cells on inkjet-printed hierarchically structured hemitoroids - Rosqvist, Emil; Fogde, Anna; Fazeli, Elnaz; Belaya, Irina; Niemelä, Erik; Määttänen, Anni; Venu, Arun P.; Kankaanpää, Pasi; Eriksson, John E.; Peltonen, Jouko (Elsevier BV, 2026)
Two-component polymer particle dispersions can be used to make nanostructured coatings with diverse applications. In this study, blends of polystyrene and acrylonitrile butadiene styrene latex dispersions were formulated for inkjet printing. When printed onto glass coverslips with a 50 µm drop spacing (DS) the result was ultrathin, nanostructured coatings. Increasing the DS to 100 µm produced arrays of nanostructured hemitoroids approximately 30–60 µm in diameter. By adjusting the blend ratio, the nanotopography of the hemitoroids could be tuned (e.g. Sq 6–32 nm).
These hemitoroid arrays, which exhibited different nanotopographies, were used for studying the influence of nanotopography on the morphology of focal adhesions (FAs) of human dermal fibroblast cells. Statistically significant differences in FA shape (e.g. roundness and aspect ratio) and size (area and perimeter length) were observed for different latex blends — even when the difference in RMS roughness (Sq) was only 3.9 nm. Strong correlations were observed between FA morphology and surface roughness in terms of Sa, Sq, Sdr, Spk, and Sk (R2 ≥ 0.9 and Pearson’s r ≥ |0.95|), indicating that the response in FA morphology was mainly driven by nanoscale height variations and fine texture of these surfaces. These findings hence highlight the role of nanotopography in modulating substrate-cell signal transduction.